Genetic Factors in Rasmussen’s Encephalitis Characterized by Whole-Exome Sequencing - Ai, Junhong; Wang, Yisong; Liu, Dong; Fan, Dongying; Wang, Qiqi; Li, Tianfu; Luan, Guoming; Wang, Peigang; An, Jing (Frontiers in Neuroscience, 2021)
Rasmussen’s encephalitis (RE) is a rare chronic neurological disorder characterized by unihemispheric brain atrophy and epileptic seizures. The mechanisms of RE are complex. Adaptive immunity, innate immunity and viral infection are all involved in the development of RE. However, there are few studies on the role of genetic factors in the mechanisms of RE. Thus, the objective of this study was to reveal the genetic factors in the mechanisms of RE. Whole-exome sequencing (WES) was performed in 15 RE patients. Ten patients with temporal lobe epilepsy (TLE), which is a common and frequently intractable seizure disorder, were used as the controls. Thirty-one non-silent single nucleotide variants (SNVs) affecting 16 genes were identified in the RE cases. The functions of the genes with SNVs were associated with antigen presentation, antiviral infection, epilepsy, schizophrenia and nerve cell regeneration. Genetic factors of RE were found first in this study. These results suggest that RE patients have congenital abnormalities in adaptive immunity and are susceptible to some harmful factors, which lead to polygenic abnormal disease.